Computer security and penetration testing - Basta, Alfred (Course Technology, Cengage Learning, 2014)
Delivering up-to-the-minute coverage, Computer Security And Penetration Testing, Second Edition offers readers of all backgrounds and experience levels a well-researched and engaging introduction to the fascinating realm of network security. Spotlighting the latest threats and vulnerabilities, this cutting-edge text is packed with real-world examples that showcase today's most important and relevant security topics. It addresses how and why people attack computers and networks - equipping readers with the knowledge and techniques to successfully combat hackers.